2019
DOI: 10.1097/ncq.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Nurse Leader Safety Rounds to Promote Highly Reliable Care

Abstract: Background: Despite decades of intensive resource allocation to eliminate preventable harm and increase high reliability in the hospital, the prevalence of serious harm remains consistent. Local Problem: A hospital reduced targeted preventable harms using audit and feedback (A&F) but failed to globally reduce harm or increase proactive awareness. Nurse leaders lacked a defined process for identifying errors, mitigating risk, and teaching systems thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…1). 8,19,30–36 Data extraction for these studies is available in Appendix B, http://links.lww.com/JPS/A352 and quality assessment in Appendix C, http://links.lww.com/JPS/A353.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 8,19,30–36 Data extraction for these studies is available in Appendix B, http://links.lww.com/JPS/A352 and quality assessment in Appendix C, http://links.lww.com/JPS/A353.…”
Section: Resultsmentioning
confidence: 99%
“…We identified articles from 9 health care organizations that reported effects of HRO initiative implementation on patient safety, safety culture, and/or other process outcomes (Table 3). 8,19,[30][31][32][33][34][35][36] Of note, only 1 study explicitly described using one of the implementation frameworks described earlier (i.e., the IHI framework). 30 Of the 9 studies, 4 stood out as implementing the most comprehensive, multicomponent HRO initiatives.…”
Section: Effects Of Hro Implementationmentioning
confidence: 99%
“…One study carried out a qualitative content analysis of the registered incidents of a hospital incident reporting system 53 ; another also uses quantitative thematic analysis to show an increase in awareness of high-reliability principles among staff. 54 Data collection mostly focuses on practices of organizational members. Six of the 7 studies aim to measure the improved reliability in the pursuit of a rather particularistic goal such as improving patient safety in a specific setting.…”
Section: Qualitative Measurementsmentioning
confidence: 99%
“…A few studies reported on positive effects of work relationship factors such as peer pressure in the forms of healthcare professionals' reminding each other to wear protective equipment [25], physicians acting as positive role models to other staff members on hand hygiene [30], nurse leaders modelling practicing safety rounds to staff [39] or collegial support from senior medical and nursing staff to junior professionals to improve adherence to standardization practices in the emergency department [71]. When physicians perceived that hospital rules were suggested through dialogue higher levels of compliance were reported [41].…”
Section: Work Relationship Factorsmentioning
confidence: 99%
“…Several studies reported that the level of adaptation or compliance with hospital standardization practices was in uenced by the level of support healthcare professionals received by their clinical leadership [25,30,34,61,63,66,72]. Leadership support was understood as 'making rounds on the units and offering words of encouragement' to follow infection prevention guidelines and policies [25] p10 and by modeling compliance to standardization practices [25,30,39,66].…”
Section: Leadership Supportmentioning
confidence: 99%